Health aspects of peanuts as an outcome of its chemical composition - Rabiatu Bonku; Jianmei Yu (Food Science and Human Wellness)
Peanut is an energy dense food item and it contains a substantial amount of fat, proteins, carbohydrate, both fat soluble and water soluble vitamins, minerals and phytochemicals. Peanuts are consumed worldwide due to its high nutritional value and pleasant or unique flavor after roasting or boiling. The lipid, protein and carbohydrate not only provide energy, but also provide essential nutrients for normal body functions such as body fat and muscle buildup. Vitamins are needed for normal cell function, growth, development, disease prevention and act as coenzymes during the production of energy. Due to the high nutrient contents of peanuts, they have been used to combat malnutrition in most developing countries. Epidemiologic studies have associated nut consumption with a reduced incidence of cardiovascular heart diseases and gallstones in both genders and diabetes in women. Limited evidence also suggests beneficial effects on hypertension, cancer, and inflammation. The health risk associated with peanut consumption is allergy in developed countries. The review discusses the health aspects, including allergy, of peanut consumption as they related to the chemical composition of peanuts using literatures published in past two decades with exceptions of a few older articles. Keywords: Peanuts, Health aspects, Nutrients, Vitamins, Peanut allergy